Rotating thermal flows in natural and industrial processes - Lappa, Marcello (Wiley, 2012)
"In this context, it is expressly shown how the aforementioned isomorphism between small and large scale phenomena becomes beneficial to the definition and ensuing development of an integrated comprehensive framework allowing the reader to understand and assimilate the underlying quintessential mechanisms without requiring, however, familiarity with specific literature on the subject"--